Complete chloroplast genome of Tulipa buhseana (Liliaceae) - Xiuting Ju; Nan Tang; Guomin Shi; Rongchun Ye; Zhiqiang Hou (Mitochondrial DNA. Part B. Resources, 2020)
The complete chloroplast genome of Tulipa buhseana was sequenced and reported here. The circular genome of T. buhseana is 152,062 bp in length and contains 133 functional genes consisting of 87 coding sequences, 38 tRNA genes, and 8 rRNA genes. With 1 species from Smilacaceae and 1 species from Alstroemeriaceae as outgroup, phylogenetic relationships of 8 Liliaceae species based on their chloroplast genomes indicated that T. buhseana is closest to T. altaica.